Effect of Good Corporate Governance Mechanism on Company Profitability Ratios - et. al., Sakina Ichsani , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Determining good corporate governance mechanisms’ effect on profability of company specifically companies that are a part of property and real estate sub-sector which also exist on the list that belongs to the Indonesia Stock Exchange (IDX) from year 2014-2019 is the purpose of this research. Purposive sampling is used as a research method, 12 companies are involved as sample. The results showed that the GCG-forming variables consisting of institutional share ownership, managerial share ownership, board of directors, independent board of commissioners and audit committee do have effect on company profitability. The profitability of said company wouldnt even be partially affected by institutional share ownership, managerial share ownership, board of directors and independent commissioners. Meanwhile, the audit committee partially affects the company's profitability. It is important for investors to look more into the aspects of Good Corporate Governance as a consideration in investing. Further researchers are expected to conduct research on Good Corporate Governance against profitability by taking a sector other than Real Estate and Property.